SlGSTE9 participates in the stability of chlorpyrifos resistance in Spodoptera litura. Issue 12 (14th August 2021) - Li, Dongzhi; He, Chengshuai; Xie, Lanfen; Ge, Xing; Deng, Tianfu; Li, Songwei; Li, Guangling; Xu, Li
Abstract: BACKGROUND: Spodoptera litura is an important agricultural pest and has developed serious resistance to multiple insecticides. The resistance level to several insecticides is reported to be unstable, but the mechanism is less reported. RESULTS: Chlorpyrifos and phoxim resistance level in a field‐collected population of S. litura declined continuously from the first to the tenth generation and remained stable at the 11th and 12th generations without insecticide exposure. Synergist experiment showed that diethyl maleate and piperonyl butoxide significantly increased mortality to chlorpyrifos and phoxim in the first and sixth generations, but not in the 12th generation. The expression of 31 identified glutathione S ‐transferase (GST) genes in the third‐instar larvae of S. litura in the first, sixth and 12th generations was determined, and eight genes were seen to decrease significantly in the sixth and 12th generations compared with the first generation. SlGSTe9 was selected for further functional study as it had higher abundance and significantly higher expression in the chlorpyrifos‐resistant population than in the susceptible population. The recombinant protein of SlGSTE9 showed metabolism activity to chlorpyrifos in vitro and in Escherichia coli, but not to phoxim. Silencing of SlGSTe9 increased the cumulative mortality to chlorpyrifos significantly. SlGSTE9 also showed antioxidant activity to cumene hydroperoxide. CONCLUSION: Our results suggest that SlGSTe9 is directly involved in chlorpyrifos resistance stability, but not in phoxim. SlGSTE9 may also participate in insecticides resistance by relieving the oxidase stress induced by insecticides. © 2021 Society of Chemical Industry. Abstract : Chlorpyrifos and phoxim resistance were unstable in a field‐collected population of Spodoptera litura in the absence of insecticides. SlGSTE9 participated in the stability of chlorpyrifos resistance, but not phoxim.